Centrosome aberrations as a possible mechanism for chromosomal instability in non-Hodgkin's lymphoma - Krämer, Alwin; Schweizer, Silja; Neben, Kai; Giesecke, Christian; Kalla, J.; Katzenberger, T.; Benner, Axel; Müller-Hermelink, H. K.; Ho, Anthony Dick; Ott, G. (Leukemia, 2003)
Recently, centrosome aberrations have been described as a possible cause of aneuploidy in many solid tumors. To investigate whether centrosome aberrations occur in non-Hodgkin's lymphoma (NHL) and correlate with histologic subtype, karyotype, and other biological disease features, we examined 24 follicular lymphomas (FL), 18 diffuse large-B-cell lymphomas (DLCL), 33 mantle cell lymphomas (MCL), and 17 extranodal marginal zone B-cell lymphomas (MZBCL), using antibodies to centrosomal proteins. All 92 NHL displayed numerical and structural centrosome aberrations as compared to nonmalignant lymphoid tissue. Centrosome abnormalities were detectable in 32.3% of the cells in NHL, but in only 5.5% of lymphoid cells from 30 control individuals (P<0.0001). Indolent FL and MZBCL contained only 25.8 and 28.8% cells with abnormal centrosomes. In contrast, aggressive DLCL and MCL harbored centrosome aberrations in 41.8 and 35.0% of the cells, respectively (P<0.0001). Centrosomal aberrations correlated to lymphoma grade, mitotic, and proliferation indices, but not to the p53 labeling index. Importantly, diploid MCL contained 31.2% cells with abnormal centrosomes, while tetraploid samples harbored centrosome aberrations in 55.6% of the cells (P<0.0001). These results indicate that centrosome defects are common in NHL and suggest that they may contribute to the acquisition of chromosomal instability typically seen in NHL.
Gesehen am 03.12.2021